Dielectric-loaded trapezoidal toothed log-periodic antenna - Patre S.R.; Singh S.P. (My University, 2025)
In this article, dielectric-loaded metal trapezoidal toothed log-periodic antenna (TTLPA) is described. The dielectric material, Rogers RT/duroid 6010 (εr = 10.2, tan δ = 0.0023) of thickness = 5 mm and of same shape as TTLPA is placed on top of conventional metal TTLPA which provides enhanced bandwidth and/or miniaturizes its aperture size without degradation in gain. The dielectric loading increases the effective length of antenna, and therefore, extends its operating frequency towards lower frequency side which miniaturizes aperture cross-section of antenna with slight increase in its thickness. The simulated input and radiation characteristics of TTLPA without and with dielectric loading are compared. The comparative studies show that the proposed antenna is 38.78% smaller in respect of aperture cross-section as compared with conventional antenna having almost identical bandwidth of 8.6 GHz (2.2–10.8 GHz) and gain variation over the range 1.5–6.1 dBi. The proposed antenna of aperture size 48.9 × 48.9 mm2 provides −10 dB reflection coefficient bandwidth of 8.6 GHz (2.2–10.8 GHz) and gain variation in the range 1.3–5.7 dBi whereas the conventional antenna of same aperture size achieves somewhat reduced bandwidth of 7.6 GHz (3.2–10.8 GHz) and gain variation in the range 1.6–5.0 dBi over the operating frequency range. © 2016 Wiley Periodicals, Inc.